DEVELOPING SCIENTIFIC APPROACH-BASED E-MODULE ASSISTED BY KSOFT FLIPBOOK MAKER APPLICATION FOR THE TENTH-GRADE OF SENIOR HIGH SCHOOL STUDENTS - Nurfajriyah Nurfajriyah; Nina Suzanne; Sirajul Munir (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
The limitations of the teaching materials, the absence of sample questions, individual assignments, and evaluations of narrative text materials are the issues covered in this study. This research aims to describe the needs of teachers and students for an electronic module (e-module) based on the scientific approach, to develop a prototype for an e-module based on the scientific approach, and to describe the experts’ validation of the e-module. This study employed R&D using the 4D development model, which has four stages: define, design, develop, and disseminate. Three validators—two lecturers and one teacher—were used to evaluate the e- module. This research findings show as follows. Firstly, teachers and students need narrative text e-module teaching materials employing a scientific approach, secondly, the e- module narrative text prototype adheres to the scientific approach. Finally, the validation test on e-module narrative text for English learning is categorized as valid. These findings recommend that using the scientific approach-based e-module narrative text material that was developed with the help of the KSOFT flipbook maker is imperatively implemented in teaching a narrative text in the tenth grade of Senior High School.